Eat the rich / P J O'Rourke - O'Rourke, P. J.
The nation's leading political satirist traverses the world, exploring the power of money, ruminating on the world's varieties of capitalism and socialism, and offering his own hilarious primer on economics. The book explains the fundamentals of economics. The author traveled the world from Wall Street to Main Street, from Shanghai to Albania, in search of the ultimate answer to the question, "Why do some economies thrive, while others just suck?" America's favorite political humorist leads readers on a hysterical whirlwind tour, from the "good capitalism" of Wall Street to the "bad socialism" of Cuba, in search of an answer to the age-old question: "Why do some places prosper and thrive, while others just suck?"